Association between anxiety disorder, anxiolytic drugs, and risk of incident Parkinson’s disease - Xiaoyan Hao; Zhiyun Wang; Yanmei Feng; Mengjie Li; Chenwei Hao; Yuanyuan Liang; Chunyan Zuo; Xuhong Yang; Dongrui Ma; YangYang Wang; Shuangjie Li; Shasha Qi; et al. (npj Parkinson's Disease)
Abstract In this prospective cohort study, we analysed data from 502,364 participants (ages 40–69) in the UK Biobank, with follow-up until 2024. Logistic and Cox regression analysis identified generalized anxiety disorder (GAD) and obsessive-compulsive disorder (OCD) as independent risk factors for Parkinson’s disease (PD), with post-traumatic stress disorder (PTSD) patients under 71 also at increased risk. Panic disorder (PAD) showed no association with PD. Further analysis of anxiolytic drug use revealed that selective serotonin reuptake inhibitors (SSRIs), benzodiazepines (BDZs), medium-to-high frequency use of tricyclic antidepressants (TCAs) and serotonin norepinephrine reuptake inhibitors (SNRIs) were linked to PD incidence, while low-frequency use of TCAs and SNRIs was not. Mediation analysis indicated that GAD influenced PD risk through the thalamus, brainstem, and left putamen, while OCD and PTSD affected PD risk via brain regions including the angular gyrus, thalamus, and postcentral gyrus. These findings provide novel insights into PD mechanisms and potential therapeutic targets.